(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study is based on the importance of these physical components in supporting the performance of volleyball game techniques such as smash, block, and serve. To evaluate the effectiveness of the training program implemented by the Jayaraya Volleyball Club of Sidoarjo Regency in increasing arm muscle strength, abdominal muscle endurance, and leg muscle explosive power in junior volleyball athletes. The study used a quasi-experimental approach with a one-group pretest-posttest design. The research sample consisted of 17 male junior athletes who participated in the training program for six weeks, with a frequency of twice a week. Measurements were carried out through push-up, sit-up, and vertical jump tests. The analysis showed a significant increase in the three physical components tested, with a significance value (2-tailed) <0.05 in all variables. The results of this study are that the Jayaraya Volleyball Club training program is effective in improving the main physical components that support athlete performance, and can be used as a reference for developing more optimal training programs in the future.